Observational case series on the clinical performance of the Variable Angle Clavicle Plate and Clavicle Hook Plate 2.7 systems: a study protocol - Jaeger, Martin; Sußiek, Julia; Beeres, Frank; Carroll, Eben; Conlan, Todd; Cunningham, Daniel; Arnhold, Richard; Lambert, Simon (Frontiers in Surgery, 2026)
BackgroundReoperation rates in clavicular fractures and acromioclavicular (AC) joint dislocations are high, often indicated for plate removal due to plate prominence and poor cosmesis. The recently designed 2.7 mm variable angle locking compression plate (VA-LCP®) Clavicle Plate and 2.7 mm VA-LCP® Clavicle Hook Plate (J&J MedTech) are intended to have an improved plate-to-bone fit, are precontoured, and have a low profile. Additionally, the Clavicle Hook Plate has a more anatomically adapted hook design to reduce the risk of painful osteolysis leading to earlier plate removals. All screw holes in these plates accept 2.7 mm screws. Primary objectives of this observational, post-marketing, prospective, multicenter case series are to gather early and mid- to long-term evidence on the clinical performance, safety, and usability of the 2.7 mm VA-LCP Clavicle Plates and 2.7 mm VA-LCP Clavicle Hook Plates, specifically to describe (1) safety, (2) clinical performance, (3) functional outcomes, (4) patient-reported outcomes (PROs) and (5) usability and surgeons' experience with the devices.MethodsApproximately 76 patients with clavicle fractures and primary surgical treatment with the 2.7 mm VA-LCP Clavicle Plate or 2.7 mm VA-LCP Clavicle Hook Plate will be enrolled prospectively over 15 months. Outcome measures include adverse events related/potentially related to the investigational device, clinical performance, functional outcomes (QuickDASH), PROs (PROMIS® upper extremity score, local pain, discomfort, and plate prominence), and radiographic outcomes. Data will be collected at baseline, 2w, 6w, 3m, 6m, 1y and 2y after surgery. The surgeons' experience with and perceived utility of the devices will be surveyed. Interim analysis will be performed when 30 patients per group have reached 6 months after surgery. Long-term outcomes will be evaluated using 2-year follow-up results. A Statistical Analysis Plan will be prepared before final analysis summarizing the descriptive statistics to be used.DiscussionThe study described in this protocol on patients with clavicular fracture or AC joint dislocations undergoing surgical fracture fixation aims to gather first evidence on the clinical performance, safety, and usability of the 2.7 mm VA-LCP Clavicle Plates and 2.7 mm VA-LCP Clavicle Hook Plate Systems. This study will provide valuable data from a standard-of-care setting and may help design future comparative studies for relevant performance parameters.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT04921865?term=NCT04921865%20&rank=1, identifier NCT04921865.